Corrosion studies of Inconel 617 in high temperature air and He-ppmO2 atmospheres - Haoxiang Li; Wei Zheng; Bin Du; Huang Zhang; Huaqiang Yin; Xuedong He; Tao Ma; Xingtuan Yang (Nuclear Engineering and Technology)
Air ingress accident is one of the typical accident conditions in Very High Temperature Reactors (VHTRs). This work investigates the oxidation kinetics, corrosion behavior and mechanism of Inconel 617 alloy in different oxygen concentration atmospheres under air ingress accident. The impact of O2 concentration and oxidation time of the alloy corrosion is investigated. A gas chromatograph was used to measure the impurity content in real time during the helium experiments. After the experiments, the alloys were characterized by electronic balance, were analyzed by Scanning Electron Microscopy (SEM), Energy-Dispersive X-ray Spectroscopy (EDS), X-ray diffraction (XRD) and carbon and sulfur analyzer. The results show that: the Inconel 617 alloy undergoes similar oxidation behavior and the degree of oxidation is very close in three groups of atmospheres with large differences in oxygen content; the alloy should show two oxidation mechanisms, linear oxidation and parabolic oxidation, during the oxidation process; the parabolic rate constant kp and kt of the alloy is a constant value and does not vary with large changes in oxygen concentration, but when the experimental temperature changes, the oxidation rate constants of the alloy change, and the lowering of the temperature leads to the lowering of the oxidation rate constants; When experimental temperature is at 950 °C, the alloy continues to undergo a “microclimatic reaction” in the atmosphere of He-ppmO2, and the microclimatic reaction disappears when the experimental temperature is lowered to 750 °C; In He-ppmO2 environment, gas chromatograph can be used instead of thermogravimetric analyzer for real-time monitoring.